Las Mareas Rojas - Jorge R. Rey (EDIS)
ENY-851S, a 5-page illustrated fact sheet by Jorge R. Rey, is the Spanish version of ENY-851, “Red Tides” (forthcoming). It explains what these “harmful algal blooms” are, what causes them, their impacts on marine ecosystems, human health, and coastal economies, and strategies for mitigation and control. Includes references.